Building COPD care on shaky ground: a mixed methods study from Swedish primary care professional perspective - Sara Lundell; Malin Tistad; Börje Rehn; Maria Wiklund; Åsa Holmner; Karin Wadell (BMC, 2017)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a public health problem. Interprofessional collaboration and health promotion interventions such as exercise training, education, and behaviour change are cost effective, have a good effect on health status, and are recommended in COPD treatment guidelines. There is a gap between the guidelines and the healthcare available to people with COPD. The aim of this study was to increase the understanding of what shapes the provision of primary care services to people with COPD and what healthcare is offered to them from the perspective of healthcare professionals and managers. Methods The study was conducted in primary care in a Swedish county council during January to June 2015. A qualitatively driven mixed methods design was applied. Qualitative and quantitative findings were merged into a joint analysis. Interviews for the qualitative component were performed with healthcare professionals (n = 14) from two primary care centres and analysed with qualitative content analysis. Two questionnaires were used for the quantitative component; one was answered by senior managers or COPD nurses at primary care centres (n = 26) in the county council and the other was answered by healthcare professionals (n = 18) at two primary care centres. The questionnaire data were analysed with descriptive statistics. Results The analysis gave rise to the overarching theme building COPD care on shaky ground. This represents professionals driven to build a supportive COPD care on 'shaky' organisational ground in a fragmented and non-compliant healthcare organisation. The shaky ground is further represented by uninformed patients with a complex disease, which is surrounded with shame. The professionals are autonomous and pragmatic, used to taking responsibility for their work, and with limited involvement of the management. They wish to provide high quality COPD care with interprofessional collaboration, but they lack competence and are hindered by inadequate routines and lack of resources. Conclusions There is a gap between COPD treatment guidelines and the healthcare that is provided in primary care. To facilitate implementation of the guidelines several actions are needed, such as further training for professionals, additional resources, and improved organisational structure for interprofessional collaboration and patient education.